1979
DOI: 10.1016/s0022-5347(17)56765-8
|View full text |Cite
|
Sign up to set email alerts
|

Carcinoma of the Prostate: Local Control with External Beam Radiation Therapy

Abstract: Local clinical control of the primary disease was evaluated in 209 patients with stage C adenocarcinoma of the prostate treated with definitive external beam radiation therapy and followed for a minimum of 2 years. Of these patients 92 per cent required no further prostatic operations for obstruction. Prostatectomy before therapy did not necessarily prevent later prostatic obstruction from occurring. Of 129 patients who had only a needle biopsy before irradiation 90 per cent had improvement of the obstructive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

1981
1981
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(13 citation statements)
references
References 17 publications
3
10
0
Order By: Relevance
“…The goal of therapy in stage C prostate cancer is local control of the tumor and prolongation of the interval free of disease [65,66]. The present data show that local control of the disease was achieved rapidly in all except one patient (98.6%).…”
Section: Stage Csupporting
confidence: 49%
“…The goal of therapy in stage C prostate cancer is local control of the tumor and prolongation of the interval free of disease [65,66]. The present data show that local control of the disease was achieved rapidly in all except one patient (98.6%).…”
Section: Stage Csupporting
confidence: 49%
“…It is remarkable that the incidence of subvesical obstruction by urethral strictures is 5–9% after transurethral resection of benign prostatic hyperplasia [8, 9], 8–19% after percutaneous radiation of prostate cancer [10, 11, 12, 13, 14] and 57% after antiandrogen (estrogen) therapy of prostatic cancer [15]. …”
Section: Discussionmentioning
confidence: 99%
“…Gibbons et al 17 in their study confirmed that prostate cancer patients who had been treated with curative external beam radiotherapy (EBRT) were less likely to suffer haematuria, 2 years following treatment, than the untreated patients. However, patients who have had previous EBRT are unable to have any further radiotherapy due to the high risk of significant localized tissue damage.…”
Section: Discussionmentioning
confidence: 95%